EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DI SMPN 5 SATU ATAP TEMPUNAK KABUPATEN SINTANG DI SMP - Marsiana Sela Triani; Sri Buwono; Fy Khosmas Fy Khosmas (Universitas Tanjungpura, 2019)
AbstractThis study aims to find out the effectiveness of the Jigsaw cooperative learning used conventional learning models. The form of this researchwas quasi-experimental with a nonequivalent control group design. The technique of data collection was observation sheet technique and the tool of data collection was a test in form of multiple-choice test. The research hypothesis showed that using one sample ttest with α = 5% obtained Zhitung= 5,415 (Ztest>Ztable), located in the area of rejection of Ho. It showed that a significant difference between the learning outcomes of students taught using the Jigsaw type cooperative learning model and those treated with the used conventional learning models. In the experimental after implemented by using jigsaw as a model cooperative learning experienced. It found out an increase in the averagescore of 61.76 pre-test to the average score of post-test 85. It was also an increase in the percentage of completeness from the score of the percentage of completeness pre-test 29.41% the post-test percentage score becomes 100%.So, it can be concluded that learning by using jigsaw as a model in the material to introducing ASEAN countries in eight students at SMPN 5 one roof, there was a highly significant effect learning outcomes of students with the difference in score percentage of completeness 70.59% and with the score of effect size 1,16. Keywords: Cooperative Jigsaw, Effectiveness, Learning Model